Combined Factor VIII And Plasma Exchange Therapy In The Management Of Patients With Factor VIII Inhibitors - Wensley, R T; Stevens, R F; Burn, A M (Thrombosis and Haemostasis, 1981)
Five patients with Haemophilia A and Factor VIII inhibitors and three patients with spontaneous Factor VIII inhibitors presented with severe or life-threatening haemorrhage. All, except one, received intermittent high dose human Factor VIII therapy combined with one or more plasma exchanges. The exception was a patient with spontaneous Factor VIII inhibitors who was plasma-exchanged without receiving Factor VIII. The five Haemophilia A patients showed a uniformly good clinical response to treatment with complete resolution of their bleeding episodes. Their inhibitors were reduced to a level approaching zero and adequate plasma Factor VIII levels were achieved. In contrast, the three patients with spontaneous Factor VIII inhibitors failed to show any clinical response to therapy. They had measurable plasma Factor VIII levels before the Factor VIII therapy, but the administered Factor VIII produced no additional increment. Their inhibitor levels were only minimally altered by therapy. Studies of the inhibitors from the haemophiliacs showed complete Factor VIII neutralisation in incubation mixtures, but inhibitor plasmas from the spontaneous cases failed to completely neutralise the admixed Factor VIII. It is postulated that in haemophiliacs with antibodies, replacement therapy is associated with the formation of stable imnune complexes which remain in the intravascular space and are removed at subsequent plasma exchange. These complexes do not show coagulant or anticoagulant activity. However, in non-haemophiliacs with acquired Factor VIII inhibitors, weaker association of Factor VIII and antibody in the immune complexes may account for the measurable plasma Factor VIII activity, and also enable the dissociated antibody to diffuse out of the intravascular space and hence be unavailable for removal by plasma exchange.